Physical education and sports into the primary school curriculum -analytical study- - Djaballah, Salim; Meziane cherif, Khabbab; Addar, Zohra; bourenane, Khalil (sports creativity, 2023)
This research paper aims to analyze the physical and sports education curriculum for the primary level, considering the sensitivity of the stage and the importance of the subject, which is no less than the importance of the rest of the school subjects, And because of its effective role in developing learner independence, And in creating a balanced and harmonious personality with its surroundings, It is a subject that values all individual resources, It transforms automatic movement into an organized and controlled movement, It helps to develop the psychological, emotional and cognitive aspects of the learner, It also helps him to discipline and respect others and to acquire the values of tolerance and love of effort, Controlling and directing excess energy, In view of the same importance, the Algerian educational curricula - similar to the educational curricula in the countries of the world - obliged the teaching of physical education and sports for all male and female students from the beginning of school to the end of secondary education, embodying the essential role of education in working to provide conditions that allow the harmonious growth of the bodies of students, And develop their physical and manual abilities as stipulated in the Education Directive.